Development of a Pteris vittata L. compound database by widely targeted metabolomics profiling. (26th March 2021) - Nguyen Thi, Kieu‐Oanh; Nguyen, Ngoc‐Lien; Pham, Hoang‐Nam; Sawada, Yuji; Hirai, Masami Yokota; Dauwe, Rebecca; Dijoux‐Franca, Marie‐Geneviève
Abstract: The objective of this work was the development of a detailed, extensive and reliable database of the metabolomes of P. vittata . Using an ultra‐performance liquid chromatography–triple quadrupole tandem mass spectrometry system (UPLC‐QqQ‐MS/MS) and based on the knowledge of retention time and mass spectral characteristics of an in‐house collection of authentic standards, we screened for the presence of a large collection of natural compounds. The database represents 359 authenticated metabolites, comprising 220 primary and 139 secondary metabolites (70 flavonoids, 16 phenylpropanoic acid derivatives, five coumarins, two stilbenoids, 14 benzoic acids, nine phenols, 20 alkaloids and three terpenoids). Comparison of the accumulation of these compounds in two tissues showed that the aerial parts were enriched in flavonols, whereas the subterranean parts were enriched in anthocyanins. The comprehensive database developed here will be beneficial in improving the understanding of the chemical basis of plant therapeutic profile using multivariate analysis, with a particular example of antioxidant activity.